Effect of finite edge radius on ductile fracture ahead of the cutting tool edge in micro-cutting of Al2024-T3 - Melkote, Shreyes N. (2009)
Evidence of ductile fracture leading to material separation has been reported recently in ductile metal cutting [S. Subbiah, S.N. Melkote, ASME J. Manuf. Sci. Eng. 28(3) (2006)]. This paper investigates the effect of finite edge radius on such ductile fracture. The basic question of whether such ductile fracture occurs in the presence of a finite edge radius is explored by performing a series of experiments with inserts of different edge radii at various uncut chip thickness values ranging from 15 to 105 m. Chip–roots are obtained in these experiments using